The Battle of Adwa : Reflections on Ethiopia's Historic Victory against European Colonialism. - Milkias, Paulos; Metaferia, Getachew (Algora Publishing, 2005)
In the 19th-century "Scramble for Africa," when the Europeans carved up an entire continent for exploitation, Africans won a solitary, shocking, glorious victory at Adwa (Ethiopia). The most celebrated military operation involving the Africans and the Europeans since the time of Hannibal, this emblematic victory still resounds in the minds of Africans and the African diaspora as a promise of potential and an illustration of the dictum, "strength in unity." In this volume, nine scholars analyze the unique Ethiopian victory at Adwa, pondering the factors that brought success, the putative missed opportunities for securing the future integrity of the Ethiopian territory, and the lessons to be learned. Rising above their regional rivalries and local concerns, all facets of this multi-ethnic society pulled together to defeat the Italian invaders who were armed with vastly more sophisticated technology and had the support of all of Europe. For the victors it was decisive; for the vanquished, catastrophic. The Italian colonialist soldiers were crushed. Their casualty figure was 70%; all their artillery pieces were captured, one out of four of their generals was taken prisoner and two of the remaining as well as almost half of their staff officers were killed on the battlefield. The event and its implications have much to say about Ethiopia's subsequent development, the secession of Eritrea, and relations with external powers. It also reveals much about the machinations of global powers and the dangers they pose to weaker nations, and most specifically international influence in Africa. The Ethiopian victory at the Battle of Adwa has remained a very important event in the shared recollection of the entire African people. It is the only secular episode in the whole history of Africa that has been celebrated for more than a century with unabated popular enthusiasm. A phenomenon such as Adwa is a complex nexus of various historical processes with wide ranging but as yet not fully explored meanings. The contributors to this collection show that Adwa does not only reflect its time, but that it also transcends it, and that the aspirations and meanings that flow from it have been a powerful constitutive force in the rise and evolution of modern Africa Indeed, it is an event that awakened the hope for emancipation and the struggle against colonialism and racism among Africans in the colonies and in the Diaspora.